Financial literacy, stock market participation, and financial well-being in Germany - Tabea Bucher-Koenen; Bennet Janssen; Caroline Knebel; Panagiota Tzamourani (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
We examine financial literacy in Germany and its relevance for financial well-being. Using data from the Panel on Household Finances collected in 2021, we show that about 62% of German households answer the Big Three financial literacy questions correctly. Those with lower education, who are out of the labor force, women, and those living in East Germany have lower levels of financial literacy. Identifying groups with lower financial literacy and developing strategies to reach them and enhance their abilities should therefore be an integral part of the German national financial literacy strategy. Financial literacy is linked to financial well-being: we document that those with higher financial literacy have a higher stock market participation rate and are less likely to report financial difficulties.
Keywords: G53; D14; G51; I3; 330; Financial knowledge; financial well-being; inflation; investment behavior